Realization of “Language is Creative” in ELT - Joni Alfino (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
It cannot be denied that Chomsky’s theory − Language is Creative − is reflected in ELT, including in writing skill in three different conditions. The first condition is when English language learners want to choose a topic to write. If the students are given a chance to choose a topic to write, they certainly will write what they have had in mind and avoid writing what is beyond their thought. When they have decided to write what is coming to their mind, it means that they are performing language creativity because they have created their own style in expressing something. This process, in fact, meets Chomsky’s theory (1968) considering the freedom given to the students to write their own ideas as the implementation of language creativity. The second condition is when the language learners are writing down the string of their coherent sentences with the variation of grammar and vocabulary. Developing a sentence requires a grammatical pattern. Composing several sentences probably needs various grammatical patterns. It means that the more the sentences are developed, the more various the grammatical patterns will be used. Related to the implementation of “Language is Creative”, this point is one of examples because the students here are required to employ various grammatical patterns and vocabulary creatively. The third condition is when the language learners are editing what they have written down. It often happens that someone is editing his works while he is writing something and so are the English language learners. When they find something inappropriate in their works, they will revise it immediately. In addition, it usually happens that they will begin writing the new one when they find that what they have written completely does not meet their hope. The process of editing carried out by the language learners when they are writing shows language creativity they have because they can feel which one is appropriate or not. From the three points stated above, it is clear that Chomsky’s theory, Language is Creative, is realized in English language teaching.